(untitled) (Journal of the College of Basic Education, 2022)
The civilizational heritage of the Arabs had an impact on the building of the maritime power of the Muslims in the Arab Islamic State on the Mediterranean coasts. After The Islam soldiers liberated the lands of the Arabic West, they turned their attention to the liberate of Andalusia in order to spread Islam to all peoples and nations. And the first soldiers of Islam arrived to the north of Andalusia. The naval force also proved its activity in mobilizing Arab-Islamic fleets and in the management of war battles against the Byzantine Roman invaders and its high ability in jihad and continued Islamic conquests on the European continent